Completing Your Doctoral Dissertation/Master's Thesis in Two Semesters or Less - Ogden, Evelyn Hunt (Rowman & Littlefield Publishers, 1997)
A long-term bestseller, this book is a pragmatic step-by-step guide to completing you dissertation or thesis during two semesters, in fifty workdays or less. It covers advisor and topic selection, proposal development, data collection and organization, available assistance, writing, and defense. The author demystifies the process and provides you with essential guidance through the rites of passage that are an integral part of completing your degree.